2014
DOI: 10.3389/fpsyg.2014.00845
|View full text |Cite
|
Sign up to set email alerts
|

Proximity and gaze influences facial temperature: a thermal infrared imaging study

Abstract: Direct gaze and interpersonal proximity are known to lead to changes in psycho-physiology, behavior and brain function. We know little, however, about subtler facial reactions such as rise and fall in temperature, which may be sensitive to contextual effects and functional in social interactions. Using thermal infrared imaging cameras 18 female adult participants were filmed at two interpersonal distances (intimate and social) and two gaze conditions (averted and direct). The order of variation in distance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…According to the emotions theory developed by Lang, Bradley, and Cuthbert (2005), valence and arousal are the key factors in this field. Previous studies (Ioannou, Morris, et al, 2014;(Salazar-López et al, 2015)) suggest that positive images increase facial temperature whereas negative images lower it. However, for the arousal effect on facial temperature, previous studies showed incongruent results as we described in the introduction.…”
Section: Experiments 2: Thermal Markers Of Phobia and Anxietymentioning
confidence: 94%
See 1 more Smart Citation
“…According to the emotions theory developed by Lang, Bradley, and Cuthbert (2005), valence and arousal are the key factors in this field. Previous studies (Ioannou, Morris, et al, 2014;(Salazar-López et al, 2015)) suggest that positive images increase facial temperature whereas negative images lower it. However, for the arousal effect on facial temperature, previous studies showed incongruent results as we described in the introduction.…”
Section: Experiments 2: Thermal Markers Of Phobia and Anxietymentioning
confidence: 94%
“…This lower nose temperature has been related to stress and increased sympathetic activity. However, in other studies, high arousal has been associated with increased nose temperature also in the case of negative emotions, lie detection, mental effort, crying, ostracism, or direct gaze (Ioannou, Morris, Baker, & Gallese, 2016;Ioannou, Morris, et al, 2014;Panasiti et al, 2016;Paolini, Alparone, Cardone, van Beest, & Merla, 2016). Different authors frequently related this thermal effect (the augmented nose temperature) to a complex autonomic interaction between the sympathetic and parasympathetic nervous systems or to residual effects probably due to a withdrawal of the sympathetic alpha-adrenergic vasoconstriction effect (Ebisch et al, 2012;Ioannou et al, 2016;Moliné et al, 2017;Tyler et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Previous research on interaction behavior and gaze aversion in interactions has shown that conversational partners usually gaze at each other to see whether the partner follows the conversation and avert their gaze in order to regulate the conversation's level of intimacy . Similarly, prolonged eye contact is assumed to be perceived as threatening or aggressive, and staring at a conversational partner's face over a longer span of time thus carries negative connotations . This might have motivated the participants to fixate on the background as well, instead of only fixating on the relevant object and the agent.…”
Section: Discussionmentioning
confidence: 99%
“…Levine et al [6], for example, reported rapid (300 ms) periorbital warming and cheek cooling after a fright response caused by a sudden, strong noise; this startle-induced thermal signature is mediated by the sympathetic nervous system (SNS). More complex emotions are driven by ostracism [10], guilt [11], social [12] and gaze contact [13], & 2017 The Author(s) Published by the Royal Society. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%